2011
DOI: 10.1111/j.1439-0523.2011.01915.x
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance of resistance to sunflower broomrape (Orobanche cumana Wallr.) in an interspecific cross between Helianthus annuus and Helianthus debilis subsp. tardiflorus

Abstract: With 2 tables Abstract Sunflower broomrape (Orobanche cumana Wallr.) constrains sunflower cultivation in many areas of Europe and Asia. Populations classified as race G that overcome all known resistance genes have recently appeared. The objective of this research was to study the inheritance of resistance to broomrape race G in a resistant accession of Helianthus debilis subsp. tardiflorus. Heads of H. debilis subsp. tardiflorus were emasculated and pollinated with pollen of the Helianthus annuus‐susceptible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 8 publications
2
38
0
2
Order By: Relevance
“…So, it should soon become clearer what resistance genes are necessary in sunflower varieties. Resistance sources have so far been cultivated sunflower or other annual Helianthus species (Velasco et al, 2011) In contrast with downy mildew, where introduction of resistances from wild H. annuus is relatively easy, if broomrape resistance requires interspecific crosses, the procedure for introduction of genes from such origins will require new research. More general knowledge of how best to make the most of the 50 Helianthus species which exist would be of great benefit to research on many breeding objectives.…”
Section: Broomrapementioning
confidence: 99%
“…So, it should soon become clearer what resistance genes are necessary in sunflower varieties. Resistance sources have so far been cultivated sunflower or other annual Helianthus species (Velasco et al, 2011) In contrast with downy mildew, where introduction of resistances from wild H. annuus is relatively easy, if broomrape resistance requires interspecific crosses, the procedure for introduction of genes from such origins will require new research. More general knowledge of how best to make the most of the 50 Helianthus species which exist would be of great benefit to research on many breeding objectives.…”
Section: Broomrapementioning
confidence: 99%
“…However, the terminology used for race identification is to some extent confusing because the same race classification is used in Genetic studies on resistance to broomrape in sunflower have confirmed in most cases control of the trait by single dominant genes, as expected for a gene for gene interaction. This has been reported for races E (Vranceanu et al, 1980;Ish-Shalom-Gordon et al, 1993;Lu et al, 2000;Pérez-Vich et al, 2004;Sukno et al, 1999), F (Pacureanu-Joita et al, 2004;Pérez-Vich et al, 2002), and G (Velasco et al, 2012). Full demonstration of the occurrence of a gene-forgene interaction in the O. cumana-sunflower was provided by Rodríguez-Ojeda, Pineda-Martos et al (2013), who showed that O. cumana race E avirulence in presence of the resistance gene Or5 was inherited as a single dominant gene.…”
Section: Genetics Of Resistance and Avirulence: The Gene-for-gene Intmentioning
confidence: 80%
“…is not particularly complex. Velasco et al (2012) identified resistance to broomrape race G in an accession of H. debilis ssp. tardiflorus that was successfully introgressed into cultivated sunflower.…”
Section: Genetics Of Resistance and Avirulence: The Gene-for-gene Intmentioning
confidence: 99%
“…Subsequently, a single dominant race G resistance gene was transferred from H. debilis ssp. tardiflorus into a cultivated background (Velasco et al, 2012).…”
Section: Introductionmentioning
confidence: 99%